The Influence of Inflation, Interest Rates, Dividend Policy on Stock Prices in the Infrastructure and Transportation Sector in East Java - Desi Kurniawati (Athallah Publishing Globalindo, 2025)
Infrastructure and transportation companies experienced a decline in stock prices a few years ago. This can be triggered by inflation, interest rates, and the company's dividend policy. Inflation and interest rates that change every year and dividend policy which is a measurement of profits earned by companies. The purpose of this study was to look at how inflation, interest rates, and dividend policies affect a company's share price. This research involves all companies in the field of infrastructure and transportation, the sampling criteria are as follows: companies listed in the foam securities from 2020-2024, companies uploading financial statements in 2020-2024, and companies that regularly distribute dividends in 2020-2024. 12 companies were selected through purposive sampling. This study was descriptive and quantitative and analyzed using several tests: normality, multicollinearity, heteroscedasticity, autocorrelation, linear regression, and T (Partial) test. The data was processed with the SPSS 24 analysis tool. The results showed that if inflation does not affect stock prices as indicated by the t-test, then the inflation value is 0.561 > 0.05. The interest rate has no effect on the stock price, as evidenced by the T-test obtained an interest rate value of 0.278 > 0.05. Dividend policy affects stock price, as seen in the T-test of the SIG value of dividend policy of 0.004 < 0.05.